A kind of ship fuel tank and its preparation method

CN120206592BActive Publication Date: 2026-10-27SHANDONG CHAMBROAD WOODEN BASE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510566724.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2026-10-27
Estimated Expiration
2045-04-30

AI Technical Summary

Technical Problem

[0003]传统层压木以天然木材为原材料制作而成,将经挑选的山毛榉木切削成薄片,在真空下浸渍酚醛树脂,经过热压机压制后固化,这种经高温高压缩合固化的加工工艺使木材塑化;但在使用过程中具有易发生霉腐变质、产品力学性能不佳、且粘接成型不能保证其整体均一性等问题;即便采用国外进口的层压木,仍面临层压木供货周期较长、材料来源短缺等问题;且现有世界上可以压制最大厚度的层压木为320mm,大部分使用场景也必须通过粘接才可达到标准使用尺寸

Benefits of technology

[0049]1.根据本申请船燃料舱用承木的制备方法,利用真空加压浸渍法对木材单板进行改性,通过限定真空与加压的压力条件,能够在相同持胶量的前提下相较于常温常压浸渍节约4~8倍浸渍时间,有效提高了船用承木的生产效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120206592B_ABST
    Figure CN120206592B_ABST
Patent Text Reader

Abstract

The application discloses a kind of ship fuel tank and its preparation method for bearing wood, belong to laminated wood manufacturing technical field.Preparation method includes: S1, vacuum pressure impregnation: after vacuumizing under negative pressure, injection adhesive is carried out to modified veneer by pressure impregnation treatment and glue draining, and modified veneer is obtained;S2, drying pre-pressing: after low-temperature drying of modified veneer, it is laid and pre-pressed to obtain assembly board;S3, press curing: the assembly board is gradiently pressurized and temperatureed to obtain laminated wood;S4, after-heat cold-pressing curing: after the pressure of the laminated wood of press curing is released, the veneer coated with adhesive on both sides is laid in the middle of the two obtained laminated woods, and the bearing wood is obtained by cold-pressing treatment.The bearing wood prepared by the method has superior mechanical properties, flame retardance and insulation, greatly improves the preparation efficiency of the bearing wood, reduces energy waste, and makes the application range of the bearing wood more extensive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a support timber for ship fuel tanks and its preparation method, belonging to the field of laminated wood panel manufacturing technology. Background Technology

[0002] Marine support timbers are used in the fuel tanks of large ships such as steamships to support independent liquid cargo tanks. Due to their long-term exposure to harsh working environments, they must withstand complex loads from the liquid cargo tanks. In order to protect the safety of the fuel tanks, the materials must meet the requirements of high compressive and shear strength, low coefficient of linear expansion, low density, low hygroscopicity, low coefficient of friction, low thermal conductivity, a wide permissible operating temperature range, and good insulation performance of the support materials.

[0003] Traditional laminated wood is made from natural wood. Selected beech wood is sliced ​​into thin sheets, impregnated with phenolic resin under vacuum, and then cured after being pressed in a hot press. This high-temperature, high-compression curing process plasticizes the wood. However, it suffers from problems such as susceptibility to mold and decay, poor mechanical properties, and inconsistent uniformity in the bonded form. Even with imported laminated wood, issues like long supply cycles and material shortages persist. Furthermore, the thickest laminated wood currently available is 320mm, meaning most applications require bonding to achieve standard dimensions. Therefore, researching ways to improve laminated wood preparation methods, optimize veneer resin holding capacity during impregnation, reduce production costs, and shorten supply cycles is crucial. Summary of the Invention

[0004] To address the aforementioned issues, a method for preparing ship fuel tank support timber is provided. This method improves the warping characteristics of laminated wood, enhances its mechanical properties, simplifies the preparation process, shortens the preparation cycle of laminated wood, and increases production efficiency, thus resolving the current problem of long delivery cycles for ship support timber.

[0005] According to one aspect of this application, a method for preparing a ship fuel tank support timber is provided, comprising the following steps:

[0006] S1. Vacuum pressure impregnation: After the veneer is vacuumed under negative pressure, adhesive is injected, pressure impregnation is performed and the adhesive is drained to obtain modified veneer;

[0007] S2. Drying and pre-pressing: The modified veneer is dried at low temperature and then laid out and pre-pressed to obtain the assembled veneer;

[0008] S3. Pressing and curing: The preform is pressed and cured under gradient pressure and temperature to obtain laminated wood;

[0009] S4. Residual heat cold pressing and curing: After depressurizing the pressed and cured laminated wood, a veneer with double-sided adhesive is laid between two pieces of the obtained laminated wood, and cold pressing is performed to obtain the supporting wood.

[0010] The gradient pressure and temperature pressing curing process in step S3 is as follows:

[0011] (1) Under the initial conditions of 5MPa and 100℃, perform 4 to 6 continuous pressurizations, with each pressurization increment being 1 to 2MPa, and hold the pressure for 10 to 20 minutes after each pressurization.

[0012] (2) Maintain pressure, raise temperature to 130-140℃, and hold for 10-30 minutes;

[0013] (3) Maintain pressure, raise temperature to 160-170℃, keep warm for 10-30 minutes, and stop heating.

[0014] Specifically, in step (1) of S3, the holding time after each pressurization is related to the thickness of the billet plate, and the holding time required after each pressurization is 3.4 min / mm; the heat preservation time in steps (2) and (3) is related to the thickness of the billet plate, and the heat preservation time required is 6 min / mm, and the total time does not exceed 30 min.

[0015] Specifically, in step (2) of step S3, heat preservation begins when the core layer temperature is >130℃; in step (3) of step S3, heat preservation begins when the core layer temperature is >160℃, and the core layer temperature is kept below 165℃ to prevent wood carbonization.

[0016] This method employs a three-stage gradient pressure and temperature-increasing pressing and curing process: In the first stage, the preform is pressed, requiring 4-6 stages of pressure increases until the preform reaches the specified thickness. The main purpose of this stage is to allow moisture and air to escape from the preform, enabling the adhesive to flow evenly along the evaporation path before curing, dispersing evenly throughout the material and improving the uniformity of the pressed material and the overall adhesive holding capacity. In the second stage, maintaining pressure while raising the temperature to 130-140℃ softens the preform and allows the adhesive to initially cure. This maintains the preform's pressing thickness while allowing the laminated wood to initially take shape, ensuring the material doesn't shift during the pressure holding process. In the third stage, pressure is maintained, and the temperature is further increased while maintaining the preform's pressing thickness to fully cure the adhesive, eliminating internal stress and elasticity within the wood, resulting in laminated wood with stable thickness and resistance to deformation.

[0017] During the three-stage pressing and curing process, the uniformity of the thickness of each veneer layer in the pressed board can be ensured by gradually increasing the temperature and pressure, thereby ensuring the overall uniformity of the laminated board. This results in good mechanical properties of the final laminated wood, making it less prone to delamination, cracking, or splitting. At the same time, due to the filling and sealing of the board by the adhesive, the sealing, waterproofing, and insulation properties of the laminated wood are also improved.

[0018] The vacuum pressure impregnation process employed in this solution, by controlling the vacuum level and pressure conditions, allows the adhesive to fully penetrate into the micropores of the wood veneer. Under vacuum conditions, some air, free water, and adsorbed water inside the veneer are extracted, resulting in an overall intracellular pressure lower than atmospheric pressure. After adhesive injection, the increased pressure allows the liquid molecules of the adhesive to better overcome capillary resistance, creating favorable conditions for adhesive penetration and reducing interface defects caused by water and air. Simultaneously, the pore structure inside the veneer becomes more open, making it easier for the adhesive to enter the micropores and resulting in a more uniform distribution of the adhesive within the veneer. Furthermore, under vacuum conditions, the cell morphology becomes more uniform, and the two phospholipid membranes on the inner side of the cell wall are in a semi-open, uniform state. The substances inside cannot move in a vacuum, so the repulsion reaction of phospholipids cannot function, allowing liquid molecules in the adhesive to overcome capillary resistance and enter the micropores of the veneer. During the pressure impregnation process, the pressure causes the adhesive to spread evenly inside the board, avoiding excessive or insufficient adhesive in certain areas, and further compressing any residual air bubbles. This ensures that the adhesive fills all pores, allowing it to bond tightly to the inner walls of the veneer pores, forming a uniform and dense sealing layer. This prevents the product from malfunctioning due to excessive water absorption during use, avoids water absorption and swelling of marine timber, and improves the stability and safety of fuel tanks.

[0019] Using a pre-pressing process with heating before pressing can solve the problem of uneven stress in veneers, and significantly improve the warping performance of veneers. At the same time, it reduces the brittleness of veneers and prevents them from cracking during subsequent pressure curing. In addition, although the pre-pressing process does not produce a curing effect due to the slight heating and pressure treatment of the assembled board, it can activate the impregnated adhesive, release the air bubbles in the adhesive, and further promote the penetration of the adhesive impregnated on the board surface into the board interior under pressure, thereby increasing the adhesive holding capacity of the board.

[0020] The laminated wood obtained by cold-pressing and curing using the residual heat of pressing has consistent strength in the vertical and adhesive directions, exhibiting excellent uniformity in mechanical properties and broadening the application range of laminated wood. Simultaneously, using the residual heat of pressing to cure the laminated wood fully utilizes the thermal resources of the production process, reducing energy waste. Furthermore, it eliminates the need for stacking and curing between laminated wood sections assembled into load-bearing timbers, effectively saving production time, improving production efficiency, and alleviating to some extent the problem of long supply cycles for marine load-bearing timbers in the market.

[0021] Optionally, the adhesive in step S1 is prepared from the following components by weight: 100-500 parts of alcohol-soluble phenolic resin, 10-25 parts of epoxy resin, 2-5 parts of curing agent, and 10-50 parts of aramid dispersion.

[0022] The mass ratio of the alcohol-soluble phenolic resin to the epoxy resin is (20-30):1.

[0023] Alcohol-soluble phenolic resin, as the main component of adhesives, has linearly arranged molecular chains, good fluidity, and can spread more evenly on the surface of veneer, which is more conducive to penetrating into the veneer channels and fibers. At the same time, alcohol-soluble phenolic resin has strong wettability and high molecular chain flexibility, which can combine with the surface of veneer through physical adsorption or van der Waals forces. Under pressure, it disperses, flows and extends to form a continuous whole, reducing interface defects. Finally, it is cured under heating conditions to form a dense and uniform impregnated body.

[0024] This solution limits the types and proportions of adhesive components. Alcohol-soluble phenolic resin has good moisture resistance and heat resistance, while epoxy resin has good toughness and waterproof performance. At the same time, the two resins work together with aramid fiber. With the participation of the curing agent, the alcohol-soluble phenolic resin and epoxy resin can cross-link after being cured by pressure and temperature increase. This further improves the weather resistance and mechanical properties of the adhesive and the board after they are combined, forming a high-performance adhesive with high strength, high toughness, moisture resistance, insulation, and fire resistance.

[0025] This solution achieves optimal results and significantly improves the overall performance of the material by adjusting the proportions of the above components. When the ratio of alcohol-soluble phenolic resin to epoxy resin is too high, the resulting board has high strength but correspondingly high brittleness and insufficient flexibility. When the ratio of the two is too low, on the one hand, the strength of the board will decrease due to the high amount of epoxy added, and on the other hand, the dispersion of the resin will also be affected, thereby reducing the uniformity of the final impregnated product performance.

[0026] Specifically, the average molecular weight of alcohol-soluble phenolic resin is 1000-1200 g / mol, the average molecular weight of epoxy resin is 3700-5400 g / mol, and the mass fraction of aramid in the aramid dispersion is 2‰-5‰.

[0027] The phenolic resin with this molecular weight limit can overcome capillary resistance under vacuum conditions, impregnate into the microstructure of wood, and penetrate into the cell cavities and cell walls of wood more efficiently under high pressure conditions, filling the pores and microcracks of wood, thereby improving the integrity of the microstructure of wood and ultimately improving the mechanical properties of laminated wood and supporting wood.

[0028] During the heating and pressurization process, epoxy resin and phenolic resin cross-link, which improves the bonding strength and further enhances the water resistance and durability of the timber.

[0029] Specifically, the curing agent is one or more of phenolic resin, dicyandiamide, acylhydrazine curing agents (such as adipic dihydrazine), and phthalic anhydride.

[0030] Specifically, the adhesive preparation process is as follows: Epoxy resin and phenolic resin are mixed together in a specified ratio and stirred thoroughly to avoid localized high or low concentrations. Excessive stirring should be avoided to prevent the introduction of too many air bubbles. After mixing, an appropriate amount of curing agent is added and mixed evenly, and finally, aramid dispersion is added.

[0031] Preferably, the aramid is para-aramid, which can increase the strength and hardness of the sheet material, while also providing good insulation properties.

[0032] Optionally, in step S1, the negative pressure condition for vacuuming the single board is 0.04 to 0.08 MPa, and the negative pressure holding time is 30 to 60 min;

[0033] The conditions for pressure impregnation treatment of single veneers are 0.68–3 MPa, and the pressure holding time is 2–4 h.

[0034] The negative pressure and pressurization conditions specified in this scheme allow the adhesive to fully penetrate the veneer and distribute more evenly. If the negative pressure is less than 0.08 MPa, the adhesive will not be able to overcome capillary resistance effectively, resulting in uneven distribution. If the pressurization pressure is too high, it may damage or break the cell walls of the wood, which is not conducive to the subsequent pressurization and curing process, and may even lead to inconsistent deformation of the assembled board, causing instability or easy deformation of laminated wood or laminated wood products.

[0035] Optionally, the glue application time for the veneer is 0.5 to 1 hour.

[0036] Specifically, the veneer coating process can be performed using air blowing and / or rotary coating.

[0037] Optionally, in step S3, the total time of the heating process in process (2) is determined by the thickness of the billet, and the heating process requires 2.5 min / mm; the total time of the heating process in process (3) is determined by the thickness of the billet after pressing and shaping, and the heating process requires 2.5 min / mm.

[0038] Specifically, 2.5 min / mm means that for every 1 mm increase in the thickness of the laminated wood, the corresponding heating time increases by 2.5 min.

[0039] Optionally, in step S2, the low-temperature drying conditions are a temperature of 55-75℃ and a relative humidity of 30-40%; the pre-pressing process is pre-pressing at 65-85℃ and 1-4MPa for 4-12 hours.

[0040] Pre-pressing the precast board under these conditions allows it to be subjected to uniform force in all directions and maintain this force for a period of time. This results in a more uniform and dense arrangement of the internal vessels and cells of the wood without damaging the cell walls of each veneer, improving the uniformity of veneer stress and reducing brittleness, thus providing better internal conditions for subsequent pressure curing.

[0041] Optionally, the pressure of the cold pressing process in step S4 is 10-18 MPa, and after standing for 1-2 hours, it is stacked and stored for 7 days.

[0042] Optionally, the veneer is preferably a beech veneer with a moisture content of 6-8%; the modified veneer is dried at low temperature after modification to a moisture content of ≤5%.

[0043] High-hardness beech veneer is selected as the raw material for the support timber. With the combined action of the cured adhesive, it has the characteristics of not being easily deformed and having high mechanical strength, which meets the requirements of support timber for ship fuel tanks.

[0044] Optionally, the laying method described in step S2 is that the fiber direction of the same layer of veneer is consistent, and the fiber direction between layers is perpendicular; this laying method enables the laminated wood to have considerable mechanical properties in two directions perpendicular to the thickness direction, thereby improving the adaptability of the laminated wood to pressure in all directions during use.

[0045] In step S4, the veneer is laid in the following manner: the fiber direction of the two veneers on the upper and lower laminated wood end faces is consistent, and the fiber direction of the middle veneer is perpendicular to that of the two veneers on the laminated wood end faces.

[0046] This paving method ensures the consistency of stress in all parts of the supporting timber in the thickness direction, preventing deformation or breakage of the supporting timber due to inconsistent stress when under load.

[0047] According to another aspect of this application, a ship fuel tank support timber is provided, which is prepared by the above method.

[0048] The beneficial effects of this application include, but are not limited to:

[0049] 1. According to the preparation method of the ship fuel tank support timber of this application, the wood veneer is modified by vacuum pressure impregnation. By limiting the vacuum and pressure conditions, the impregnation time can be saved by 4 to 8 times compared with room temperature and pressure impregnation under the same glue holding capacity, which effectively improves the production efficiency of ship support timber.

[0050] 2. According to the preparation method of the ship fuel tank support timber of this application, after pressing, the laminated wood is cured and spliced ​​using the residual heat of pressing, which saves the time of stacking and curing the laminated wood before splicing, without affecting the mechanical properties of the ship support timber. This not only improves the production speed, but also reuses the heat energy required in pressing, reduces energy waste, fully improves the production efficiency of ship support timber, and alleviates the problem of long supply cycle of ship support timber.

[0051] 3. The preparation method of the ship fuel tank support timber according to this application combines a heated pre-pressing process with a gradient heating and pressing process, which solves the problems of uneven stress and warping of the veneer, avoids the occurrence of delamination, cracking or splitting of the laminated wood during the pressing process, and improves the mechanical properties of the laminated wood. At the same time, it improves the uniform distribution of the adhesive attached to the board inside the board, and improves the impregnation and sealing effect of the adhesive on the micropores of the board, thereby reducing the water absorption rate and improving the insulation of the support timber product. In addition, the laying method specified in this solution makes the mechanical properties of the final ship support timber uniform in all directions, with good uniformity, and can be used in various size applications, thus broadening the application range of support timber.

[0052] 4. According to the preparation method of the ship fuel tank support wood of this application, by combining the composition limitation of the adhesive with the preparation process conditions, the adhesive is uniformly distributed in the wood veneer and between the boards. This not only improves the final mechanical properties, waterproof and flame-retardant properties of the support wood, but also improves the durability of the laminated wood. This makes the carbon sequestration effect of tree growth and wood use more lasting, which can promote the sustainable use of forest resources, maximize its carbon sequestration benefits, and reduce carbon emissions. Attached Figure Description

[0053] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings:

[0054] Figure 1 These are fluorescent images of the modified single-plate used in the experimental examples of this application;

[0055] Figure 2 This is a schematic diagram of the veneer and laminated wood installation method involved in the embodiments of this application. Detailed Implementation

[0056] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0057] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application were all purchased commercially.

[0058] Unless otherwise specified, the methods used in the embodiments and comparative examples of this application are conventional methods in the prior art.

[0059] The alcohol-soluble phenolic resin used in the following examples has an average molecular weight of 1100 g / mol, the epoxy resin has an average molecular weight of 4500 g / mol, and the aramid dispersion has a mass fraction of 3‰.

[0060] In the following embodiments and comparative examples, the installation method of veneer and laminated wood in step S4 is as follows: Figure 2 As shown.

[0061] Example 1

[0062] S1. Vacuum pressure impregnation: Place the veneer in the modification tank, evacuate and maintain a negative pressure of 0.08MPa for 60 minutes, inject adhesive so that the adhesive covers the veneer by 10cm, apply pressure of 3MPa for 4 hours, and then apply adhesive by blowing and rotating for 1 hour to obtain the modified veneer.

[0063] S2. Drying and pre-pressing: The modified veneer is dried at a low temperature of 70℃ for 6 hours in a balancing machine. When the moisture content of the veneer is ≤5%, it is laid out. The laying method is that the fiber direction of the same layer of veneer is consistent, and the fiber direction between layers is perpendicular. Then it is transferred to a pre-pressing machine and pre-pressed at 80℃ for 12 hours to obtain the assembled board.

[0064] S3, Press Curing:

[0065] (1) Place the billet into a hot press. The pressure of the hot press is 5MPa and the temperature is 100℃. Press it 6 times to increase the pressure to 18MPa so that the thickness of the billet is 50mm. Hold the pressure for 20min.

[0066] (2) While maintaining the pressure at 18 MPa, raise the temperature to 140℃ and hold for 20 min;

[0067] (3) While maintaining the pressure at 18 MPa, raise the temperature to 170°C, hold for 20 minutes, and then stop heating;

[0068] S4. Residual heat cold pressing and curing: After depressurizing the pressed and cured laminated wood, double-sided glued veneer is laid between two obtained assembly boards. The veneer is laid in such a way that the fiber direction of the two veneers on the upper and lower laminated wood end faces is consistent, and the fiber direction of the middle veneer is perpendicular to the fiber direction of the two veneers on the laminated wood end faces. After standing at 18 MPa for 2 hours, it is cooled and stacked for 7 days to obtain the supporting wood.

[0069] The adhesive is prepared from the following components: 500 parts alcohol-soluble phenolic resin, 25 parts epoxy resin, 5 parts curing agent, and 50 parts aramid dispersion.

[0070] Example 2

[0071] S1. Vacuum pressure impregnation: Place the veneer in the modification tank, evacuate and maintain a negative pressure of 0.04MPa for 45 minutes, inject adhesive so that the adhesive covers the veneer by 10cm, apply pressure of 2MPa for 3 hours, and then apply adhesive through air blowing and rotation for 45 minutes to obtain the modified veneer.

[0072] S2. Drying and pre-pressing: The modified veneer is dried at a low temperature of 65℃ for 5 hours in a balancing machine. When the moisture content of the veneer is ≤5%, it is laid out. The laying method is that the fiber direction of the same layer of veneer is consistent, and the fiber direction between layers is perpendicular. Then it is transferred to a pre-pressing machine and pre-pressed at 70℃ for 8 hours to obtain the assembled board.

[0073] S3, Press Curing:

[0074] (1) Place the billet into a hot press. The pressure of the hot press is 5MPa and the temperature is 100℃. Press it 5 times to increase the pressure to 14MPa so that the thickness of the billet is 50mm. Hold the pressure for 15min.

[0075] (2) Maintain pressure, raise the temperature to 135°C within 125 min, and hold for 20 min;

[0076] (3) Continue to maintain the pressure, raise the temperature to 162°C, hold for 20 minutes, and then stop heating;

[0077] S4. Residual heat cold pressing and curing: After depressurizing the pressed and cured laminated wood, double-sided glued veneer is laid between two obtained preform boards. The veneer is laid in such a way that the fiber direction of the two veneers on the upper and lower laminated wood end faces is consistent, and the fiber direction of the veneer in the middle is perpendicular to the fiber direction of the two veneers on the laminated wood end faces. After standing under 15 MPa pressure for 1.5 hours, it is cooled and stacked for 7 days to obtain the supporting wood.

[0078] The adhesive is prepared from the following components: 200 parts alcohol-soluble phenolic resin, 18 parts epoxy resin, 3 parts curing agent, and 35 parts aramid dispersion.

[0079] Example 3

[0080] S1. Vacuum pressure impregnation: Place the veneer in the modification tank, evacuate and maintain a negative pressure of 0.04MPa for 30 minutes, inject adhesive so that the adhesive covers the veneer by 10cm, apply pressure of 0.68MPa for 2 hours, and then apply adhesive through air blowing and rotation for 0.5 hours to obtain the modified veneer.

[0081] S2. Drying and pre-pressing: The modified veneer is dried at a low temperature of 60°C for 3 hours in a balancing machine. When the moisture content of the veneer is ≤5%, it is laid out. The laying method is that the fiber direction of the same layer of veneer is consistent, and the fiber direction between layers is perpendicular. Then it is transferred to a pre-pressing machine and pre-pressed at 60°C to obtain the assembled board.

[0082] S3, Press Curing:

[0083] (1) Place the preform into a hot press. The pressure of the hot press is 5MPa and the temperature is 100℃. Press it 4 times to increase the pressure to 10MPa so that the thickness of the laminate is 50mm. Hold the pressure for 10min.

[0084] (2) Maintain pressure and raise the temperature to 130°C within 125 min;

[0085] (3) Continue to maintain the pressure at 10MPa, raise the temperature to 160℃, hold for 30min, and then stop heating;

[0086] S4. Residual heat cold pressing and curing: After depressurizing the pressed and cured laminated wood, double-sided glued veneer is laid between two obtained assembly boards. The veneer is laid in such a way that the fiber direction of the two veneers on the upper and lower laminated wood end faces is consistent, and the fiber direction of the middle veneer is perpendicular to the fiber direction of the two veneers on the laminated wood end faces. After standing under 10 MPa pressure for 1 hour, the temperature is reduced and the wood is stacked and stored for 7 days to obtain the supporting wood.

[0087] The adhesive is prepared from the following components: 100 parts alcohol-soluble phenolic resin, 10 parts epoxy resin, 2 parts curing agent, and 10 parts aramid dispersion.

[0088] Example 4

[0089] The difference from Example 3 is that in S1, the negative pressure condition is 0.09 MPa.

[0090] Example 5

[0091] The difference from Example 3 is that in S1, the pressure condition is 0.5 MPa.

[0092] Example 6

[0093] The difference from Example 3 is that the number of parts of alcohol-soluble phenolic resin is 300 parts.

[0094] Example 7

[0095] The difference from Example 3 is that the number of parts of epoxy resin is 50 parts.

[0096] Comparative Example 1

[0097] The difference from Example 3 is that the single-layer modification process is performed by impregnation under normal pressure.

[0098] Comparative Example 2

[0099] The difference from Example 3 is that the veneer is placed in a modification tank without vacuuming, and only pressure impregnation is performed.

[0100] Comparative Example 3

[0101] The difference from Example 3 is that in S3, after step (1) pressurization is completed, the pressure is maintained, step (2) is omitted, and the temperature is directly raised to 160°C for curing based on step (1).

[0102] Comparative Example 4

[0103] The difference from Example 3 is that in S3, step (1) does not use a gradient pressurization process, but directly pressurizes to 10MPa, gradient heats to 160°C, and holds pressure until the specified thickness is reached.

[0104] Comparative Example 5

[0105] The difference from Example 3 is that the pressed and cured laminated wood is first subjected to cold curing for 7 days, and then subjected to heating and pressure bonding. The bonding conditions are 10 MPa, heating to 160°C and pressing and curing for 30 minutes.

[0106] Experimental Example

[0107] The modified veneer obtained in step S1 was weighed, and the impregnation amount and adhesive holding amount of the veneer were calculated. The results are shown in Table 1.

[0108] The prepared timber was subjected to mechanical property tests. Among them, the bending strength and bending modulus were tested according to "ISO178-2010 Plastics - Determination of bending properties". The test results are shown in Table 2.

[0109] The water absorption rate, electrical strength, and burning time of the prepared timber were tested. The water absorption rate was tested according to the standard "ISO 62-2008 Determination of water absorption of plastics", the electrical strength was tested according to "IEC 61061-2-1992 Test method for unimpregnated compacted laminated timber for electrical applications", and the burning time of the material was tested according to "EN ISO 9239-1 Fire resistance of flooring materials". The results are shown in Table 3.

[0110] Modified veneers with adhesive holding capacities of 25%, 35%, and 45% were also prepared, and fluorescence images were taken. (See attached images.) Figure 1.

[0111] Table 1

[0112]

[0113]

[0114] Table 2

[0115]

[0116] Table 3

[0117] Example 1 0.14 11.9 18′57″ Example 2 0.27 12.7 17′14″ Example 3 0.32 13.1 16′19″ Example 4 0.5 12.5 16′49″ Example 5 0.29 12 16′33″ Example 6 0.49 13.7 15′48″ Example 7 0.5 10.5 15′01″ Comparative Example 1 0.5 11 8′ Comparative Example 2 0.46 12.4 17′06″ Comparative Example 3 0.41 11.5 13′13″ Comparative Example 4 0.38 11.1 11′41″ Comparative Example 5 0.44 10.6 10′15″

[0118] The data shows that the laminated wood obtained in Example 2 has the best overall performance in terms of mechanical strength, hydrophobicity, and fire resistance. However, considering factors such as production cost, technical feasibility, veneer glue holding capacity, and various test performances of the samples, Example 3 is the best. It is evident that this solution can obtain laminated wood materials with excellent performance by adjusting the veneer impregnation and pressing conditions of the laminated wood and combining a specified proportion of adhesive components. At the same time, the residual heat is used to bond the pressed laminated wood, eliminating the need for pressurization and heating after cooling. This saves cooling time and eliminates the need to reheat the laminated wood, thus saving energy and improving production efficiency.

[0119] The above description is merely an embodiment of this application, and the scope of protection of this application is not limited to these specific embodiments, but is determined by the claims of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of this application should be included within the scope of protection of this application.

Claims

1. A method for preparing a ship fuel tank support timber, characterized in that, Includes the following steps: S1. Vacuum pressure impregnation: After the veneer is vacuumed under negative pressure, adhesive is injected, pressure impregnation is performed and the adhesive is drained to obtain modified veneer; S2. Drying and pre-pressing: The modified veneer is dried at low temperature and then laid out and pre-pressed to obtain the assembled veneer; S3. Pressing and curing: The preform is pressed and cured under gradient pressure and temperature to obtain laminated wood; S4. Residual heat cold pressing and curing: After depressurizing the pressed and cured laminated wood, a veneer with double-sided adhesive is laid between two pieces of the obtained laminated wood, and cold pressing is performed to obtain the supporting wood. The adhesive in step S1 is prepared from the following components by weight: 100-500 parts of alcohol-soluble phenolic resin, 10-25 parts of epoxy resin, 2-5 parts of curing agent and 10-50 parts of aramid dispersion, wherein the mass ratio of alcohol-soluble phenolic resin to epoxy resin is (20-30):

1. The gradient pressure and temperature pressing curing process in step S3 is as follows: (1) Under the initial conditions of 5MPa and 100℃, perform 4 to 6 continuous pressurizations, each pressurization increment being 1 to 2MPa, and hold the pressure for 10 to 20 minutes after each pressurization. (2) Maintain pressure, raise temperature to 130~140℃, and hold for 10~30 minutes; (3) Maintain pressure, raise temperature to 160~170℃, keep warm for 10~30min, and stop heating; In step S1, the negative pressure condition for vacuuming the single board is 0.04~0.08MPa, and the negative pressure holding time is 30~60min; The conditions for pressure impregnation treatment of single veneers are 0.68~3MPa, and the pressure holding time is 2~4h; In step S4, the pressure of cold pressing is 10~18MPa, the standing time is 1~2h, then the temperature is reduced, and the material is stacked and stored for 7 days.

2. The method for preparing the ship fuel tank support timber according to claim 1, characterized in that, In step S1, the glue application time for the single board is 0.5~1h.

3. The method for preparing the ship fuel tank support timber according to claim 1, characterized in that, In step S3, the total time of the heating process in process (2) is determined by the thickness of the billet plate, and the heating process requires 2.5 min / mm; the total time of the heating process in process (3) is determined by the thickness of the billet plate, and the heating process requires 2.5 min / mm.

4. The method for preparing the ship fuel tank support timber according to claim 1, characterized in that, In step S2, the low-temperature drying time is 3-6 hours, the temperature is 60-70℃, the relative humidity is 30-40%, and the moisture content of the modified veneer after low-temperature drying is ≤5%. The pre-compression process is carried out at 60~80℃ and 1~4MPa for 4~12 hours.

5. The method for preparing the ship fuel tank support timber according to claim 1, characterized in that, The veneer is a beech veneer with a moisture content of 6-8%.

6. The method for preparing the ship fuel tank support timber according to claim 1, characterized in that, The laying method described in step S2 is that the fiber direction of the same layer of veneer is consistent, and the fiber direction between layers is perpendicular; In step S4, the veneer is laid in the following manner: the fiber direction of the two veneers on the upper and lower laminated wood end faces is consistent, and the fiber direction of the middle veneer is perpendicular to that of the two veneers on the laminated wood end faces.

7. A type of support timber for a ship's fuel tank, characterized in that, The material is prepared by the method described in any one of claims 1 to 6 for the preparation of ship fuel tank support timber.

Citation Information

Patent Citations

  • Insulating wood laminating product and preparation method thereof

    CN101941217A

  • Soft wood composite material and preparation method thereof

    CN111267201A

  • High-strength light insulating laminated board and preparation process thereof

    CN118596265A

  • Laminated board production process, laminated board and board cutting machine

    CN119283136A

  • Asymmetric container bottom plate

    CN205033328U